Cross sectional study on knowledge, attitude and practice regarding dengue among adult population visiting a tertiary care hospital in Puducherry, India - Valantine, Bershic; Kumar, R. Prahan; Vasudevan, Senthilvel; Sureshbabu, Jayanthi; Singh, Zile (International Journal Of Community Medicine And Public Health, 2017)
Background: Dengue is one of the world’s emerging and rapidly spreading pandemic disease of public health importance. High rainfall and low temperatures are associated with increased number of dengue cases. Methods: A hospital based cross sectional study was conducted between 15th August 2013 and 15th October 2013 with a sample of 200 in a tertiary care multi-speciality hospital in Puducherry using pre-designed and pre-tested questionnaire. The study protocol was approved by ICMR and Institutional (PIMS) Ethical Committee. Participants were included in the study based on the following criteria: (1) More than 20 years of age. (2) Permanent resident of Pondicherry. Results: Out of the 200 participants 68% were males and 32% were females. Most of them (64%) had gone to schools, while 9.5% were illiterates. Of the 200 participants, 180 (90%) knew that mosquito is the vector for Dengue. 162 (81%) of participants felt hospitalisation is necessary for dengue management. 80% of participants mentioned use of ceiling fan as a predominantly used preventive measure against mosquito bite, whereas 43% of them use mosquito coils to avoid mosquito bites. Majority of the respondents (66%) spend less than Rs.100 ( 1.47) in a month for various mosquito preventive measures. Conclusions: The knowledge about dengue was good, although more awareness needs to be created to identify the clinical signs of dengue. The overall attitude and practices of the participants towards dengue care, prevention and control is good.